Everolimus in adult tuberous sclerosis complex patients with epilepsy: Too late for success? A retrospective study - Stockinger, Jakob; Strzelczyk, Adam; Nemecek, Andrea; Cicanic, Michal; Bösebeck, Frank; Brandt, Christian; Hamer, Hajo; Intravooth, Tassanai; Steinhoff, Bernhard J. (Epilepsia, 2021)
Objective: There is evidence that everolimus (EVE) significantly reduces seizure frequency in epilepsy patients with tuberous sclerosis complex (TSC). Given that TSC-related proliferative processes are more dynamic during brain development, seizure outcomes of patients treated with EVE may be age-related and may be less convincing in adult patients. The aim of this study was to assess the effectiveness and the safety profile of EVE in adults in clinical practice. Methods: We performed a multicenter retrospective chart review of TSC subjects with active epilepsy who started EVE in adulthood (≥18 years of age) at seven German epilepsy centers. The primary endpoint was the retention rate after 6 months. Results: A total of 45 subjects with a mean age of 31.6 ± 11.1 years at EVE start fulfilled the inclusion criteria. Retention rate after 6 months was 98% (43/44 evaluable subjects). Response rate (seizure reduction ≥ 50%) was 33% (14/43 evaluable subjects; four completely seizure-free). We did not find a significant relationship between epilepsy outcome parameters and patient age at EVE start. Adverse events were reported in 19 subjects and were judged to be serious in six patients. Three patients died during the observation period. Significance: Evidence suggests that EVE is an effective add-on treatment for epilepsy in adult TSC patients, surprisingly without any age limit to individual benefit. A strong age-dependent effect within the period of adulthood seems unlikely. Even if there was no proof of a causal relationship between deaths and EVE intake, patients with EVE should be carefully monitored, especially for infections and stomatitis.
CRIS-Team Scopus Importer:2021-02-12
Keywords: disease-modifying therapy; epilepsy; everolimus; tuberous sclerosis complex